Association Between Total Genotype Score and Muscle Injuries in Top-Level Football Players: a Pilot Study - Myosotis Massidda; Laura Flore; Paolo Cugia; Francesco Piras; Marco Scorcu; Naoki Kikuchi; Pawel Cięszczyk; Agnieszka Maciejewska-Skrendo; Filippo Tocco; Carla Maria Calò (SpringerOpen, 2024)
Abstract Background Recently, genetic predisposition to injury has become a popular area of research and the association between a few single nucleotide polymorphisms (SNPs) and the susceptibility to develop musculoskeletal injuries has been shown. This pilot study aimed to investigate the combined effect of common gene polymorphisms previously associated with muscle injuries in Italian soccer players. Results A total of 64 Italian male top football players (age 23.1 ± 5.5 years; stature 180.2 ± 7.4 cm; weight 73.0 ± 7.9 kg) were genotyped for four gene polymorphisms [ACE I/D (rs4341), ACTN3 c.1729C > T (rs1815739), COL5A1 C > T (rs2722) and MCT1 c.1470A > T (rs1049434)]. Muscle injuries were gathered for 10 years (2009-2019). Buccal swabs were used to obtain genomic DNA, and the PCR method was used to genotype the samples. The combined influence of the four polymorphisms studied was calculated using a total genotype score (TGS: from 0 to 100 arbitrary units; a.u.). A genotype score (GS) of 2 was assigned to the "protective" genotype for injuries, a GS of 1 was assigned to the heterozygous genotype while a GS of 0 was assigned to the "worst" genotype. The distribution of genotype frequencies in the ACE I/D (rs4341), ACTN3 c.1729C > T (rs1815739) and MCT1 c.1470A > T (rs1049434) polymorphisms was different between non-injured and injured football players (p = 0.001; p = 0.016 and p = 0.005, respectively). The incidence of muscle injuries was significantly different among the ACE I/D (rs4341), ACTN3 c.1729C > T (rs1815739) and COL5A1 C > T (rs2722) genotype groups, showing a lower incidence of injuries in the "protective" genotype than "worse" genotype (ACE, p < 0.001; ACTN3, p = 0.005) or intermediate genotype (COL5A1, p = 0.029). The mean TGS in non-injured football players (63.7 ± 13.0 a.u.) was different from that of injured football players (42.5 ± 12.5 a.u., p < 0.001). There was a TGS cut-off point (56.2 a.u.) to discriminate non-injured from injured football players. Players with a TGS beyond this cut-off had an odds ratio of 3.5 (95%CI 1.8-6.8; p < 0.001) to suffer an injury when compared with players with lower TGS. Conclusions These preliminary data suggest that carrying a high number of "protective" gene variants could influence an individual's susceptibility to developing muscle injuries in football. Adapting the training load parameters to the athletes' genetic profile represents today the new frontier of the methodology of training.